Implementasi Discovery Learning dalam Pembelajaran Sistem Tata Surya di Kelas VI SDN Patrang 02 - Nayla Rizqi Kamila; Muhammad Suwigyno Prayogo; Heny Aisyafah; Dewi Indah Wulandari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to apply the Discovery Learning model in teaching the solar system in grade VI at SDN Patrang 02 Elementary School in Jember Regency. This model was chosen to overcome learning problems that are still teacher-centered and do not provide opportunities for students to think critically and discover concepts independently. Through this approach, it is hoped that students can be more active, creative, and understand the concept of the solar system more deeply through a direct discovery process. The research method used was descriptive qualitative with a participatory strategy. Activities were carried out through the stages of planning, implementation of learning, observation, and reflection with teachers and students. Data were collected through observation of learning activities, interviews with teachers, and documentation during the learning process. Data analysis was conducted descriptively to describe the effectiveness of the Discovery Learning application in improving the quality of learning.The results of the study indicate that the application of Discovery Learning can increase student active participation, critical thinking skills, and understanding of the solar system concept. Teachers also experienced an increase in their ability to design and implement student-centered learning. In addition, this activity encourages the formation of a collaborative learning culture and the growth of teacher leadership in learning innovation in elementary schools.